2018
DOI: 10.1097/md.0000000000013264
|View full text |Cite
|
Sign up to set email alerts
|

The association between statin use and endometrial cancer survival outcome

Abstract: Background: Previous studies on the association between statin use and survival outcomes in gynecologic cancers have presented conflicting results. No independent studies to elucidate the association between statin use and survival outcomes of endometrial cancer (EC) have been conducted. Methods: To gather updated evidence, we carried out an extensive literature search on Medline (PubMed and OvidSP), Embase, Cochrane Library, China National Knowledge Infrastructure (CNK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…In association with progestin therapy (local or systemic), different drugs have been investigated such as GnRH agonists, aromatase inhibitors [79], aspirin [80,81], and statins [82]. GnRH agonists combined with IUS have demonstrated satisfactory results in terms of complete response and recurrence rate.…”
Section: Other Drugsmentioning
confidence: 99%
“…In association with progestin therapy (local or systemic), different drugs have been investigated such as GnRH agonists, aromatase inhibitors [79], aspirin [80,81], and statins [82]. GnRH agonists combined with IUS have demonstrated satisfactory results in terms of complete response and recurrence rate.…”
Section: Other Drugsmentioning
confidence: 99%
“…Likewise, research indicates a reduction in morbidity, as well as a more favorable clinical course as a result of the application of drugs, such as metformin, which reduce these factors [58][59][60]. However, the results of the studies on the use of statins in EC remain inconclusive [61][62][63][64][65], and the observational studies often compare the effects of two drugs, i.e., antidiabetic metformin and a selected compound from the statins class [48,49].…”
Section: Endometrial Cancermentioning
confidence: 99%
“…Slightly different results have been presented by Li and co-workers [63]. Using electronic databases, they analysed the data of 5923 EC women from Austria, Denmark, Israel, UK and USA.…”
Section: Endometrial Cancermentioning
confidence: 99%
“…For cancers of the female reproductive organs, previous meta‐analyses have found mixed results regarding the protective effect of statins against breast cancer incidence and survival 15,19‐23 . In addition, two meta‐analyses found mixed results concerning the protective effects of statins against cervix uteri cancer 24,25 . Several meta‐analyses of epidemiological studies have also found a reduced risk of ovarian cancer incidence and mortality among statin users 26‐34 .…”
Section: Introductionmentioning
confidence: 99%